A PPENINGKATAN KOMPETENSI SISWA SMK MELALUI PEMBELAJARAN EXPERIANTIAL LEARNING BERBASIS KELAS INDUSTRI - Fania, Marini; Iriani, Tuti; Arthur, Riyan (LPPM Universitas Negeri Jakarta, 2024)
This research aims to evaluate the implementation of industrial class-based experiential learning in Vocational High Schools (SMK) and its impact on increasing student competency, which is considered crucial in facing the challenges of industrial development in Indonesia. This learning approach is expected to provide an authentic and relevant learning experience to the needs of the world of work, proven to increase students' motivation, learning outcomes and practical skills in various subjects through a literature review. However, the high unemployment rate of vocational school graduates and the lack of connection between the school curriculum and industrial demands show the urgency of developing learning models that better integrate education with industrial needs. The Systematic Literature Review (SLR) method was used to analyze ten related previous studies, showing that the experiential learning model had a positive impact on learning motivation and learning outcomes of vocational school students. However, research highlights the limitations of implementing industry-based experiential learning for it requires collaboration between schools, government and industry. Involving industry in the learning process is expected to provide students with direct experience, increasing their readiness to enter the world of work. This research contributes to detailing the benefits of industrial class-based experiential learning in vocational schools and highlights the need for increased implementation of this model. The findings of this research are the basis for further research and efforts to develop vocational education in Indonesia.